Comparison of Outcomes of Conventional Septoplasty Versus Endoscopic Septoplasty using Freer’s Incision in Symptomatic Deviated Nasal Septum - Khadgi, S.; Gurung, U.; Pradhan, B.; Tripathi, P. (Kathmandu University Medical Journal, 2021)
Background Septoplasty techniques have evolved over the years with endoscopic septoplasty gaining popularity in the recent times. Objective To compare the outcomes of conventional septoplasty with endoscopic septoplasty using Freer’s incision in symptomatic deviated nasal septum. Method It was a prospective, randomized and comparative study done at Department of ENT Head and Neck Surgery, Tribhuvan University Teaching Hospital, Kathmandu, Nepal from July 2018 to August 2019. A total of 70 patients with symptomatic deviated nasal septum were allocated randomly into two groups. Group A underwent conventional septoplasty whilst Group B underwent endoscopic septoplasty using Freer’s incision. Sino-nasal outcome test (SNOT-10) score was recorded pre-operatively and post -operatively between four to six weeks of surgery. Paired and independent ‘t’ test for mean was used as a statistical tool. Result Out of 70 patients, 57(81.43%) were males and 13(18.57%) females. The age group mostly affected was in the third and fourth decades with total 47 patients (67.14%). In the conventional group, the pre-op mean SNOT-10 score was 11.46 (SD±3.6) while post-op mean SNOT-10 score was 2.60 (SD±1.9), the difference being statistically significant (p value 0.00001). Similarly, in the endoscopic group, pre-op mean SNOT-10 score was 12.06 (SD±4.88) and post-op mean SNOT-10 score was 3.37 (SD±2.71) with the difference being statistically significant (p value 0.00001). Comparison of post-operative mean SNOT-10 score between two techniques was not statistically significant (p value 0.17). Conclusion Both conventional and endoscopic septoplasty techniques using Freer’s incision were equally effective in improving symptoms due to deviated nasal septum.